Hubungan Antara Kompetensi Andragogi Komunitas WKRI Dengan Efektivitas Program Kunjungan Pastoral Di Gereja Katolik Santo Rafael - Carlos Marselius Sihombing; Silvia Mariah Handayani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the relationship between the andragogy competency of the Wanita Katolik Republik Indonesia (WKRI) community and the effectiveness of the pastoral visitation program at Santo Rafael Catholic Church. The background of this study is grounded in the importance of pastoral companions’ ability to apply the principles of andragogy (adult learning) so that pastoral visits can be well-targeted and have a genuine impact on the members visited, particularly the elderly and those in need of spiritual accompaniment. This study employed a quantitative approach with a correlational design. The population consisted of members of the WKRI Santo Rafael branch community, with a research sample of 30 respondents and an instrument trial involving 15 respondents. The research instrument was a questionnaire measuring the variables of andragogy competency (X) and the effectiveness of the pastoral visitation program (Y), which had been tested for validity and reliability. Data were analyzed using the Spearman Rank correlation test with the assistance of SPSS. The results showed a correlation coefficient of rs = 0.376 with a significance value of p = 0.041 (p < 0.05), indicating a significant positive relationship between andragogy competency and the effectiveness of the pastoral visitation program, although classified as weak, with a coefficient of determination (R²) of 14.1%. This indicates that the better the andragogy competency possessed by the WKRI community, the more effective the pastoral visitation program implemented, although other factors beyond andragogy competency also contribute to the program’s effectiveness. Based on these findings, it is recommended that the WKRI community continue to develop the andragogy competency of pastoral companions through ongoing training to improve the effectiveness of the pastoral visitation program for its members.